House Prices In Malaysia: Demand, Supply And Inflation Hedging Ability - Yeap, Geok Peng (2018)
This study aims to examine house prices in Malaysia from three aspects which are housing demand, housing supply and housing returns over the sample period from 2000Q1 to 2015Q4. The empirical models are designed based on Autoregressive Distributed Lag (ARDL) approach. The results show that, on the demand side, house prices are mainly driven by population and quantity of housing stock, while economic factors such as income and interest rate appear to display a less significant role in determining long-run house prices in Malaysia. Government housing policy i.e. the real property gain tax appears to be ineffective in controlling house price appreciation.